2010
DOI: 10.1111/j.1475-6773.2010.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Disparity Implications of Medicare Eligibility Criteria for Medication Therapy Management Services

Abstract: Objective. To determine whether there would be racial and ethnic disparities in meeting eligibility criteria for medication therapy management (MTM) services implemented in 2006 for Medicare beneficiaries. Data Sources/Study Setting. Secondary data analyses of the Medical Expenditure Panel Survey (2004)(2005). Study Design. Logistic regression and recycled predictions were used to test the disparities in meeting eligibility criteria across racial and ethnic groups. The eligibility thresholds used by health pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 16 publications
2
64
0
Order By: Relevance
“…For instance, two recent studies have shown that (1) adherence to prescription medications treating hypertension, high cholesterol, and inflammation can reduce AL, even in older adults (Booth et al 2013), and (2) reductions in AL over time are followed by reductions in mortality risk . At the same time, non-Hispanic blacks are less likely to receive prescriptions for maintenance medications and pain medication (Institute of Medicine 2003), are less likely to qualify for Medicare coverage of medications (Wang et al 2010), are less likely to be insured (Carrasquillo et al 2000;Gaskin et al 2009;Haas et al 2003;Institute of Medicine 2003;LaVeist 2005LaVeist , 2002LaVeist et al 2007LaVeist et al , 2011Zuvekas and Taliaferro 2003), and are less likely to seek mental health assistance (Fiscella et al 2002). Such disparities in access to health-protecting resources, which are associated but not interchangeable with traditional socioeconomic variables like income and education, may explain why high baseline levels of AL may affect nonHispanic blacks to a greater extent than non-Hispanic whites.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, two recent studies have shown that (1) adherence to prescription medications treating hypertension, high cholesterol, and inflammation can reduce AL, even in older adults (Booth et al 2013), and (2) reductions in AL over time are followed by reductions in mortality risk . At the same time, non-Hispanic blacks are less likely to receive prescriptions for maintenance medications and pain medication (Institute of Medicine 2003), are less likely to qualify for Medicare coverage of medications (Wang et al 2010), are less likely to be insured (Carrasquillo et al 2000;Gaskin et al 2009;Haas et al 2003;Institute of Medicine 2003;LaVeist 2005LaVeist , 2002LaVeist et al 2007LaVeist et al , 2011Zuvekas and Taliaferro 2003), and are less likely to seek mental health assistance (Fiscella et al 2002). Such disparities in access to health-protecting resources, which are associated but not interchangeable with traditional socioeconomic variables like income and education, may explain why high baseline levels of AL may affect nonHispanic blacks to a greater extent than non-Hispanic whites.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction less likely to meet Part D utilization-based eligibility criteria for MTM services (Wang et al, 2010). Given the greater burden of CV diseases among minorities, particularly Blacks (Wong et al, 2002), potential unintended consequences of Part D benefit design and delivery structure may have especially negative consequences for these already burdened minority beneficiaries.…”
mentioning
confidence: 99%
“…Wang et al noted that minority populations utilize fewer prescriptions despite having higher rates of chronic illnesses. 56 As a consequence, there is limited data on all outcomes related to MTM for minorities and less ability to generalize findings. Studies in the literature have employed a number of differing approaches to MTM: face-to-face, telephone, and mail.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…African and Latino Americans tend to have higher rates of certain severe chronic conditions but also use fewer prescription drugs than European Americans. 56 To evalute the racial and ethnic disparities in meeting criteria of MTM services for Medicare beneficiaries, Wang et al (2010Wang et al ( , 2012) conducted a retrospective analysis of the nationally representative sample of Medicare beneficiaries in the Medical Expenditure Panel Survey (MEPS). 56,57 The results showed that the African and Latino populations were less likely to be eligible for MTM than were whites according to 2006 criteria and 2010 criteria.…”
mentioning
confidence: 99%